Age-related differences in women's foot shape. (December 2016) - Ansuategui Echeita, Jone; Hijmans, Juha M.; Smits, Sharon; Van der Woude, Lucas H.V.; Postema, Klaas
Highlights: Changes in foot shape can contribute to incorrect choices of footwear, eventually leading to foot pain and foot problems. In this study, older age in women was significantly associated with larger foot-shape measurements, mainly in the forefoot. In contrast, there was a length decrease, principally in forefoot measurements, in the highest age category (80 years and over). Findings emphasize the need for a shoe-design range geared to an adequate fit for the ageing foot. Clinicians may find these results useful in providing guidance vis-à-vis foot pain and footwear. Abstract: Purpose: Describe age-related differences in women's foot shape using a wide range of measurements and ages. Study design: Cross-sectional, observational study. Main outcome measurements: Six foot-shape measurements of each foot: foot lengths, ball widths, ball circumferences, low instep circumferences, high instep circumferences, and heel instep circumference. Results: 168 women from 20 to over 80 years of age, divided into seven age categories, were included. Older women had significantly greater foot-shape measurements, even after adjusting for Body Mass Index. Ball widths increased 3.1–4.0 mm per decade, ball circumferences 5.6–7.4 mm per decade, high instep circumferences 0.4–4.8 mm per decade, and heel instep circumferences 1.8–1.9 mm per decade. Ball widths, ball circumferences, and left high instep circumference plateaued in the 70–75 years-of-age category, and decreased in the oldest age category. For low instep circumference, age did not prevail significantly over Body Mass Index. Foot length was not associated with age. Conclusion: This study described women's progressive foot-shape changes with age. The findings provide a better understanding of foot-shape changes, mainly found in the forefoot. It demonstrates that for a good fit, shoe design for older adults and for younger adults should differ.